The PHILOSOPHICAL REVIEW OF MATERIALISM AND IDEALISM MARRIED AGE LIMITS IN INDONESIA: Study of Article 7 Paragraph (1) of Law 16 of 2019 jo. Law 1 of 1974 concerning Marriage - Ahyani, Hisam; Muharir; Permana, Dian (Universitas Islam Negeri Mataram, 2023)
This research departs from a juridical confusion regarding the ideal of a person going to get married, where the age of marriage with other provisions regarding age, namely in terms of the philosophical Materialism and Idealism of Marriage Age in Indonesia. Whereas in Indonesian Law on Marriage Marriage is only permitted if men and women have reached the age of 19 (nineteen) years. The purpose of this study is to find out the philosophical review of materialism and idealism of marriage age in Indonesia, with the article 7 paragraph (1) for 16 of 2019 jo. u 1 year 1974 regarding marriage). The conclusion of this study is the philosophical value of materialism and idealism of marriage age is the concept of historical materialism of humans who will choose the readiness of themselves in the face of marriage, this is because one's age is not a reference, which is the basis for people to get married including self-readiness to face material livelihood, readiness self and material. Likewise in Indonesia, the ideal age in society in Indonesia if it is connected with Karl Mark's theory, then the readiness of oneself in the material (economic elements) is as a reference for people to get married.